SPECIFIC TRAINING FOR THE SHOTOKAN KARATE BASED ON THE COMPETITION FIGHT - Marques Junior, Nelson Kautzner (Revista Observatorio del Deporte, 2016)
The objective of the study was to explain the specific training to the karateka improve the competition fight. The situational training the karate coach needs to prescribe the actions that occurs in the competition fight. The situational training with exercise of anticipation, two karatekas stay at the base fight, a karateka practices the attack with kick or punch and the other karateka does the anticipation with punch. The situational training of defend the attack and counter-attack, two karatekas stay at the base fight, during the exercise is combined for a karateka attack in the direction of the trunk and the other karateka needs to defend the attack and after practices the counter-attack. The combined attack training, two karatekas stay at the base fight, during the exercise is combined for a karateka perform the attack in the direction of the trunk and the other karateka needs anticipate the attack with an offensive technique or defend the attack and after practices the counterattack. The competitive training the karate athlete needs to practice the fight with situations same or similar of the competition. An important content that the karate coach should be prescribe in the situational training and in the competitive training are the practices of the motor learning - blocked practice, the random practice and mixed practice. In conclusion, the specific training based on the contents of the physical education causes an improvement in the fight and is important for the training because the session has a scientific basis.